Redefining Islamic Moderation: Trends of Islamic Labelling in Food and Song - Attaftazani, Muhammad Ikhsan; Purnama, Intan (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2021)
Abstract: Muslims are threatened by themselves for blaming each other and claiming as the right ones that follow the path of Rasulullah. This condition is worsened by the spread of caption containing hate speech to oppress other Islamic organizations and the campaign of Islamic labeling in products. The recent labeling trend in food and song has attracted Indonesian netizens in social media as expressed in two popular hashtags #LaguAnakHaram and #KleponTidakIslami. Therefore, this paper aims to answer the following questions (1) What is the effect of Islamic labeling? (2) How to deal with Islamic labeling? (3) How to practice Islamic moderation values in contemporary Indonesia? Thus, to answer the questions, this paper analyzed Islamic labeling in some products within social media. This research adhered to the qualitative method and collects data by observing the Muslim’s response to Islamic labeling. This research showed that Islamic labeling affects the spread of conjecture information about Islamic views. Besides, it will triger everyone among Islamic society or organization to blame each other. Meanwhile, to face this challenge, it is necessary to educate the Muslims especially in Indonesia about Islamic moderation by maintaining Indonesian culture. It is noteworthy that Islamic moderation has been practiced in Indonesia since the era of Walisongo—the preacher who taught Islam in Indonesia—and the teachings need to be adjusted within the disruption era. In addition, moderation is also stated in the Quran and Hadith as tawâsuṭ concept.Abstrak: Umat Islam terhambat perkembangannya karena saling menyalahkan dan mengaku sebagai orang paling benar yang mengikuti jalan Rasulullah. Kondisi ini diperparah dengan merebaknya caption berisi ujaran kebencian untuk menindas ormas Islam lainnya dan kampanye label Islami pada produk. Tren pelabelan pada makanan dan lagu akhir-akhir ini menarik perhatian netizen Indonesia di media sosial seperti yang diungkapkan dalam dua tagar populer #LaguAnakHaram dan #KleponTidakIslami. Oleh karena itu, tulisan ini bertujuan untuk menjawab pertanyaan-pertanyaan berikut (1) Apa pengaruh label Islam? (2) Bagaimana menghadapi label Islami? (3) Bagaimana mempraktekkan nilai-nilai moderasi Islam di Indonesia kontemporer? Maka dari itu, untuk menjawab pertanyaan tersebut, tulisan ini menganalisis pelabelan Islami pada beberapa produk di media sosial. Penelitian ini menggunakan metode kualitatif dan mengumpulkan data dengan melihat respon umat Islam terhadap label Islam. Penelitian ini menunjukkan bahwa pelabelan Islam mempengaruhi penyebaran informasi dugaan tentang pandangan Islam. Selain itu, akan memicu setiap orang di kalangan masyarakat atau organisasi Islam untuk saling menyalahkan. Sedangkan untuk menghadapi tantangan tersebut, perlu dilakukan edukasi kepada umat Islam khususnya di Indonesia tentang moderasi Islam dengan tetap menjaga budaya Indonesia. Patut dicatat bahwa moderasi Islam telah dipraktikkan di Indonesia sejak era Walisongo—nabi yang mengajarkan Islam di Indonesia—dan ajarannya perlu disesuaikan dengan era disrupsi. Selain itu, moderasi juga dinyatakan dalam Alquran dan Hadits sebagai konsep tawâsuṭ.